Codzienne i duchowe ścieżki kobiet środkowego Wschodu – Nepalki, Tybetanki i Bhutanki - Skrzypińska, Katarzyna (Człowiek i Społeczeństwo, 2012)
Diversity, which is characteristic feature of Middle Asia, attracts attention of tourists, adventures’seekers, scientists and others. It is so fascinating to compare the three countries – such dissimilar as Nepal, Tibet and Bhutan. The article presents everyday and spiritual life of the people and especially women from these countries, on the religious – Hindu and Buddhist – background.